Embedding from Morrey spaces to Morrey-Stummel spaces - Laweangi, Artmo Dihartomo; Gunawan, Hendra (KOMUNITAS Analisis Matematika INDONESIA, 2024)
In this paper, we study the relation between Stummel spaces, Morrey spaces, and Lebesgue spaces. We show the existence of embedding from Lebesgue spaces to Stummel spaces, and from Morrey spaces to Stummel spaces. The key of showing the existence of embeddings relies on the boundedness of Riesz potential operator both in Morrey spaces and Lebesgue spaces.